In vitro fermentation and isolation of heparin-degrading bacteria from human gut microbiota. (April 2021) - Pan, Lin; Sun, Weixia; Shang, Qingsen; Niu, Qingfeng; Liu, Chanjuan; Li, Guoyun; Yu, Guangli
Abstract: Heparin and its derivative are commonly used as injectable anticoagulants in clinical procedures, but possess poor oral bioavailability. To explore the role of gut microbiota in the poor oral effect of heparin, the degradation profiles of heparin on six human gut microbiota were investigated. The heparin-degradation ability varied significantly among individuals. Furthermore, two strains of heparin-degrading bacteria, Bacteroides ovatus A2 and Bacteroides cellulosilyticus B19, were isolated from the gut microbiota of different individuals and the degradation products of the isolates were profiled. The ΔUA2S-GlcNS6S was the major end product with almost no desulfation. 3- O -sulfo group-containing tetrasaccharides were detected, which indicated that the antithrombin binding site was broken and this explained the lost anticoagulant activity of heparin. Collectively, the present study assessed the degradation profiles of heparin by human gut microbiota and provided references for the development of oral administration of heparin from a gut microbiota perspective. Highlights: The heparin-degradation ability varied significantly among individuals. B. ovatus and B. cellulosilyticus isolated from human fecal could degrade heparin. The ΔUA2S-GlcNS6S was the major end degradation product in all isolates. The products of 3- O -sulfo group-containing tetrasacchardes were detected. Several breakdown products explained the destroyed anticoagulant activity of heparin.